Pengajaran Mekatronika Menggunakan Gambar Animasi Makromedia Flash di Jurusan Teknik Mesin - Aris Zainul Muttaqin (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2007)
Mechatronics is a subject that need understanding of many previous subject such as control, electronics,computer science, and mechanics. To achieve the subject goal, most importance is encourage student’s zealthrough implementation of automation in industry. Because every next topics and sub-topics are delicate anddifficult, to make them easily understand it needs visualization. In this research, macromedia flash is used. Theprogram is proofed able to visualize every topics succesfully, from automation in industry, digital technique,how RAM and ROM system works, animation of relay and microcontroller. Lastly, the program visualize aladder program PLC and closed loop controll.Keywords: mechatronics, animation, macromedia flash